Hubungan Sikap Terhadap Sastra Dan Kemampuan Memahami Cerita Dengan Keterampilan Menulis Deskripsi - Umbarasari, Thea (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This study aims to know whether there is a relationship between attitudes toward literature and the ability to understand the story with a description writing skills. This research was conducted at SMA Pelita Bangsa South Tangerang in February to September of the school year 2016/2017. This method which is used in this research is descriptive method with survey and correlation. The sample in this research was all students of grade X with 40 people. Attitude instrument to literature using questionnaire test by the number 40 questions, the ability to understand the story was using multiple choice test by the number 35 questions while a description writing skills using the result of writing. Before the data was analyzed first performed the trial data with the instrument test the validity and reliability testing using a correlation formula Pearson Product Moment and Point Biserial. The result of analyzing showed that: (1) based on the significance test of correlation between the pair of scores to literature (X1) with a description writing skills test (y) was obtained t=4,99>t=1,70 at a very level significance of ?=0,005, so it can be concluded that coefficient correlation r=0,629 very significance. This finding concludes that there is a relationship between attitude to literature with a description writing skills test. (2) Based on the significance test of correlation between the pair of score of ability to understand the story (X2) with a description writing skills test (Y) was obtained t=0,577 t=1,70 at level significance ?=0,05, so it can be concluded that correlation coefficient 0,577 very significance. This finding concludes that there is a positive relationship between ability to understand the story with a description writing skills test, (3) based on the result of calculation were obtained plural correlation coefficient R of 0,719 if it is consulted with Ftable list with ?=0,05 be 3,26 , so it can be concluded that plural correlation coefficient which obtained in this research is significance. These findings reject zero hypothesis, that there is no positive relationship collectively between attitudes to literature (X1), ability to understand the story (X2) with a description writing skills test (y), it?s consequently H1 accepted, that there is a positive relationship together between attitudes to literature (X1), the ability to understand story (X2) with a description writing skills test (Y). This research is expected as a contribution to teachers especially high school teachers. They should draw attention to their students aware of the importance of literature for life. Teacher can also provide exercise and homework for the students because understanding the story takes quite a long time. In presenting the subject matter to write a description of various methods should be used so that students do not get bored and it would be nice if it is supported by the media to the characteristics of learning, so that the learning process can run effectively.